Efektifitas Manajemen Pelatihan dan Pengembangan Kepemimpinan Pegawai Negeri Sipil - Rahmat, Rahmat (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2014)
Leadership training for supervisors (Diklatpim Tingkat IV) is one of the training, which is frequently implemented by public training organisations in Indonesia. This training aims at improving the supervisors’ leadership competencies in order to improve their performances. This article is a summary of the result of the research on the effectiveness of leadership training management for civil servants, implemented by two training institutions, Bandiklada Provinsi Jawa Barat and Balai Diklat PU Wilayah II Bandung. The research is intended to firstly describe the current practice, and secondly to analyze the effectiveness of leadership training management, and finally to formulate a hypothetical model of the management of leadership training for supervisors in these two training institutions. This research employed a qualitative method with three data gathering techniques, namely, interview, participant observation and document analysis. Based on the result of the data analysis, this research concludes that the management of leadership training for supervisors in these two training institutions has not been fully effective. Based on these findings, this research developed a hypothetical model used as the strategy to improve the effectiveness of leadership training management, namely, a competency-based leadership training for supervisor model, that can be implemented by these two training institutions.